The Effect of Emotional Intelligence on Self-Efficacy, Job Satisfaction, and Organizational Commitment Among Bumn Bank Frontline Employees in Jabodetabek - Bakri, Sorayanti Utami Putri; Nilasari, B. Medina; Nisfiannoor, M. (Journal Research of Social Science, Economics, and Management, 2025)
The ever-increasing level of competition in the banking industry demands the ability of frontliner employees to manage emotions and maintain organizational commitment. This research aimed to analyze the effect of emotional intelligence on self-efficacy and job satisfaction and its impact on organizational commitment among frontliner employees of state-owned banking companies in Jabodetabek. The sample in this study consisted of 200 state-owned banking frontliner employees from Mandiri, BRI, BNI, and BTN in the Jabodetabek area to obtain accurate data. Questionnaires were created using Google Forms and distributed via the WhatsApp social media platform. The unit of analysis was the employees of the state-owned banking frontliners. The data collection technique used was purposive sampling, which is a method based on the research criteria determined by the researcher. Structural equation modeling analysis was conducted using AMOS software. The results of the study show a positive and significant effect of emotional intelligence on self-efficacy and job satisfaction, which in turn impact organizational commitment among frontliner employees of BUMN banking companies in Jabodetabek. Managerial implications suggest that emotional intelligence, self-efficacy, and job satisfaction significantly influence the organizational commitment of frontliner employees in state-owned banks in Jabodetabek. Moreover, this research is highly impactful, presenting an opportunity for banking companies to further develop innovations that are increasingly modern and to attract employees to work in their companies in a comfortable, dedicated, and satisfying manner.